Culture, Identity, and Walkability: Determining Patterns of Walking Behavior in a High-risk Population (breakout presentation). (December 2017) - Goopy, Suzanne; Chapman, Jonathan; Kassan, Anusha; McCormack, Gavin; O'Brien, Mary; Silversides, Halley; Chowdhury, Tanvir Turin
Abstract : Background: Walkability, viewed from a population health intervention perspective, holds enormous promise with research showing that the more walkable a neighbourhood, the healthier its residents. How to harness this across diverse populations and identified harder-to-reach groups is a difficult question from both a social justice and equity perspective. Newcomers to Canada face a special set of barriers to leading physically active lifestyles: despite the known benefits of physical activity, studies show that the physical health of many newcomers declines significantly following their transition into the host country. While there is speculation in the research as to why this is the case – acculturation or loss of protective cultural barriers – there is a dearth of research exploring the everyday links between culture, motivation and utilitarian physical activity? Rundle, in Calgary's north-east is a community with a significant newcomer presence and a low–mid walkability score, and the site for our research. Aim: Our project explores the motivation and barriers to 'walking for health' and 'transportation walking' among first- and second-generation South Asian Canadians living in Rundle, Calgary. It highlights the interrelationships and interactions that play out between culture, identity, and walkability in determining patterns of walking behavior in a high-risk population. Method: Up to 15 participants are involved in this qualitative study. Using "engagement ethnography" this project focuses on day-to-day cultural practices and habits and their impact on the experience of walkability in the SA population in Rundle. 'Cultural probes' (cameras, maps, diaries etc.), participant observation, and semi-structured interviews elicit insights from participants on the factors that encourage or discourage the active incorporation of walking in their daily lives. Results/Conclusions: This project offers a new kind of access to an often 'hard-to-reach' community. Findings offer insights concerning actual/potential disconnects between big picture data and experiences of certain end-users.